2016
DOI: 10.1097/sla.0000000000001514
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Early Warning Score in Early Identification of Critical Postoperative Complications

Abstract: Critical postoperative complications can be preceded by rising EWS. Interventional studies are needed to evaluate whether EWS can reduce the severity of postoperative complications and mortality for surgical patients through early identification and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
0
32
0
2
Order By: Relevance
“…Early warning systems such as the Modified Early Warning Score or Rothman Index, aide in rapid screening and identification of patients at risk for clinical worsening. 9,10 Both utilize easily accessible data, are straightforward to calculate, and may be easily integrated into the EHR. These highly sensitive scores are designed to alert health care providers to all at-risk patients, but often have high false positive rates and are not specific to postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early warning systems such as the Modified Early Warning Score or Rothman Index, aide in rapid screening and identification of patients at risk for clinical worsening. 9,10 Both utilize easily accessible data, are straightforward to calculate, and may be easily integrated into the EHR. These highly sensitive scores are designed to alert health care providers to all at-risk patients, but often have high false positive rates and are not specific to postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…These highly sensitive scores are designed to alert health care providers to all at-risk patients, but often have high false positive rates and are not specific to postoperative complications. 9,10 Other widely validated risk scores for surgical patients such as the National Surgical Quality Improvement score and Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity score provide risk stratifications for selected postoperative complications. 11,12 The clinical use of these tools can be limited, as they require elaborate data collection and calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Early warning scores, on the other hand, such as the Modified Early Warning Score (MEWS) (5) and National Early Warning Score (NEWS) (6), are increasingly being used to dynamically risk stratify general ward patients (7). Recent studies in patients admitted to surgical services have found them to have good predictive accuracy for adverse events, including cardiac arrest, unplanned ICU transfer, and death (8)(9)(10)(11)(12)(13). More recently, electronic databases and advanced statistics have enabled increasingly complex early warning scores, such as the electronic Cardiac Arrest Risk Triage (eCART) score (14)(15)(16)(17), which utilizes 33 time-varying parameters including both vital signs and laboratory data and has been shown to be more accurate than MEWS in the general inpatient population (16).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Carr et al () who therefore suggested more frequent assessments of patients with high scores of pain intensity. The same approach is applied when vital signs with the early warning scores are monitored; that is, higher scores lead to more frequent measurements (Hollis et al, ). However, in contrast to actions taken following high early warning scores, decisions about intervals between pain assessments should involve the patient as pain is an individual experience.…”
Section: Discussionmentioning
confidence: 99%